A hundred years of Sociedad de Cirugía del Uruguay - Turnes, Antonio L (Cirugía del Uruguay, 2020)
The year 2020 marks the Centenary of the foundation of the Uruguayan Society of Surgery, started by young surgeons led by Carlos V. Stajano and Manuel Albo ...